Rural-Urban Migration and Its Effects on Livelihood: A Case of Urlabari Municipality, Morang. - Lamichhane, Bhim Prasad (New Journey, 2024)
This research work mainly concerns with the rural-urban migration and its effects on livelihood. The main problem of the study was to find out the rural-urban migration and its effects in Urlabari Municipality, ward no. 7. The objectives of the study were to find out the rural- urban migration ratio in Urlabari Municipality, ward no.7 and to analyse the effects of rural urban migration. This research study is quantitative in its nature. Primary resources of data were collected from 130 households who were selected purposively using questionnaire and interview. Similarly the secondary resources of data were collected from journals, articles, books, websites and other concerned organizations. The collected data were analysed with the help of computer using simple statistical tools such as percentage. It was found through the analysed data that the major causes of rural- urban migration are job/service opportunities. 23 per cent of the respondents migrated to the study area for the sake of job/ services. It was concluded that the job/services, education are the major pull factors for the rural people for their migration.